Asymmetrically committed relationships. (December 2017) - Stanley, Scott M.; Rhoades, Galena K.; Scott, Shelby B.; Kelmer, Gretchen; Markman, Howard J.; Fincham, Frank D.
This study compared romantic relationships in which there was a substantial difference (>1 SD ) in the commitment levels of the two partners to those with more equal levels. These asymmetrically committed relationships (ACRs) were studied in a national, longitudinal sample of unmarried, opposite-sex romantic relationships ( N = 315 couples); 64.8% ( n = 204) of relationships were categorized as non-ACRs, 22.8% were ACRs in which the male partner was less committed than the female partner ( n = 72), and 12.4% ( n = 39) were ACRs in which the female partner was less committed than the male partner. Those who were cohabiting or who had children together were more likely to be in ACRs than those without these characteristics. Compared to those not in ACRs, the less committed partners in ACRs (referred to as "weak links") reported lower relationship adjustment, more conflict, and more aggression in their relationships; however, these differences were explained by their low levels of commitment. The more committed partners in ACRs ("strong links") also reported lower relationship adjustment, more conflict, and more aggression than those not in ACRs, even when controlling for their levels of commitment (which were also higher, on average, than those not in ACRs); this finding is noteworthy given that high levels of commitment usually inhibit conflict and aggression. Relationships in which the female partner was the weak link were more likely to break up within 2 years (54%) than those with male weak links (29%) or non-ACRs (34%). However, asymmetrical commitment was not nearly as important a predictor of breakup as females' levels of commitment. The findings advance the understanding of asymmetrical commitment in romantic relationships and highlight the value of studying both members of a couple in research on commitment.